The Influence of Empowering Leadership and Motivation on Teachers’ Performance - Simarmata, Elisme; Wardiah, Dessy; Rahman, Andi (Yayasan Sembilan Pemuda Indonesia, 2025)
Teacher’s performance is an important element in achieving the goals of educational institutions. Therefore, educational institutions must be able to maximize the factors that can affect teacher performance, which are the principal’ empowering leadership and teacher motivation. The purpose of this study is to analyze the influence of school principal empowering leadership and teacher performance in public vocational high school in Kayuagung sub district. This study employed a quantitative method Questionnaire’s were employed as the data gathering methods in this study. Data analysis using multiple regression test. The results indicate a significant influence of teacher motivation and principal empowering leadership on teachers’ performance in vocational high schools in Kayuagung Sub-district.